The global culture of bullying : explorations and recommendations - Castleberry, Carol L. (New York, NY : Routledge, 2023)
"This book explicates 'bullying' as a concept and as a social and cultural phenomenon that has become a defining reality of the times in which we live. The author begins in the arena where it is first, and most acutely individually, experienced-in school-and expands to other institutions and areas of social life-the family, the workplace, and the local, national, and international spheres, extending of the concept of bullying to the global arena to uncover the social and institutional root causes of the extreme forms of bullying such as trafficking, torture, terrorism, and genocide. The book discusses the steps taken to address these issues and analyses their efficacy. It explores the concept of epigenetics, brain development, childhood experiences, and other psychological factors that contribute to bullying behaviours and predispositions. The book investigates and compares anti-bullying and anti-violence initiatives taken particularly in the U.S, the U.K., Scotland, and India to address the issue and create community-wide resilience practices. It also describes the current trends in decisions from international, regional, and domestic law, and offers evidence-based policy recommendations to establish a culture of respect for human dignity. An interdisciplinary, intercultural exploration and analysis of the phenomenon of bullying, this book will be of interest to students, teachers, and researchers of psychology, sociology, anthropology, social justice and law, human rights, and cultural studies. It will also be useful for academic libraries, academicians, policy planners, school administration, government officials, and readers interested in reading about bullying"--
OCLC-licensed vendor bibliographic record.
Keywords: Bullying; Bullying -- Social aspects; Human rights; PSYCHOLOGY / General; PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Anthropology / Cultural